Winning the race with aging: age-related changes in gait speed and its association with cognitive performance in dogs - Mondino, Alejandra; Khan, Michael; Case, Beth; Fefer, Gilad; Panek, Wojciech K.; Gruen, Margaret E.; Olby, Natasha J. (Frontiers in Veterinary Science, 2023)
In humans, gait speed is a crucial component in geriatric evaluation since decreasing speed can be a harbinger of cognitive decline and dementia. Aging companion dogs can suffer from age-related mobility impairment, cognitive decline and dementia known as canine cognitive dysfunction syndrome. We hypothesized that there would be an association between gait speed and cognition in aging dogs. We measured gait speed on and off leash in 46 adult and 49 senior dogs. Cognitive performance in senior dogs was assessed by means of the Canine Dementia Scale and a battery of cognitive tests. We demonstrated that dogs’ gait speed off leash, a relatively easy variable to measure in clinical settings, is correlated with fractional lifespan and cognitive performance in dogs, particularly in the domains of attention and working memory. Moreover, food-motivated gait speed off leash proves to be a more effective indicator of age-related deterioration and cognitive decline than gait speed on leash.